The role of the high representative for foreign affairs and security policy of the European Union : a critical discourse analysis on the Israeli-Palestinian conflict - Karakaş, Serra İlgi (My University, 2023)
Bu tez Avrupa Birliği Dış İlişkiler ve Güvenlik Politikası Yüksek Temsilcisi Federica Mogherini’nin İsrail-Filistin Sorunu’na ilişkin üç beyanı, bir açıklama metni ve iki konuşmasının Eleştirel Söylem Çözümlemesi (ESÇ) üzerine bir çalışma sunmayı amaçlamaktadır. Tezin ana argümanı, Avrupa Birliği Dış İlişkiler ve Güvenlik Politikası Yüksek Temsilcisi’nin oynadığı rolün, sorunun her iki tarafı için bir sorun yönetimi mekanizmasının inşa edilmesine büyük katkı sağlaması ve özellikle iki devletli çözüm için çabalamış olmasıdır. İsrail-Filistin ilişkilerinin düzelmesi için uluslararası arenada sürdürdüğü söylem oldukça yapıcı ve ilham verici olmuştur. Bu çalışma için seçilen materyallerin analizi ile Avrupa Birliği’nin (AB) İsrail- Filistin Sorunu’na yönelik dış politika gündemi ve bu doğrultuda gerçekleştirilen plan ve eylemlerden hareketle sunulacaktır. ESÇ için seçilen yöntem, Norman Fairclough’un üç boyutlu eleştirel söylem çözümlemesi yöntemidir.

This thesis aims to provide a study of Critical Discourse Analysis (CDA) of three statements, a remarks text and two speeches by the High Representative of the European Union for Foreign Affairs and Security Policy, Federica Mogherini on the Israeli-Palestinian Conflict. The main argument of the thesis is that the role played by the High Representative of the European Union for Foreign Affairs and Security Policy has contributed a lot to building a conflict management mechanism for the two sides of the conflict and strived especially for two-state solution. The discourse she maintained in the international arena for bettering the relations between Israel and Palestine has been quite constructive and inspiring. With the analysis of the selected materials for this study, the European Union’s (EU) stance towards the Israeli-Palestinian Conflict will be presented with reference to the EU’s agenda of foreign policy regarding Israel and Palestine and the plans and actions taken accordingly. The selected methodology for CDA is Norman Fairclough’s Three-Dimensional Model.
Keywords: Arab-Israeli conflict; Arap-İsrail çatışması; Avrupa Birliği Dış İlişkiler ve Güvenlik Politikası Yüksek Temsilcisi; Avrupa Birliği ülkeleri; Dış ilişkiler; Eleştirel Söylem Çözümlemesi (ESÇ); European Union countries; Fairclough’s Three-Dimensional Model; Fairclough’un Üç Boyutlu Modeli; Foreign relations; Güvenlik politikası; HighRepresentative of the European Union for Foreign Affairs and Security Policy (HR); İsrail-Filistin Sorunu Critical Discourse Analysis (CDA); Securty policy; the Israeli-Palestinian Conflict